Fasting Blood Glucose Level and Alcohol Consumption among Men in Mendawai Palangka Raya - Suratno Suratno; Novidha Muji Rahayuningrum; Helmus Helmus (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
Alcohol consumption is often associated with the incidence of diabetes mellitus. This study aimed to examine fasting blood glucose levels and alcohol consumption in men in Mendawai, Palangka Raya, Central Kalimantan. The cross-sectional study design was carried out to asses fasting blood glucose levels on 20 male alcohol drinkers. Blood glucose assay was determined by an automated enzymatic colorimetric technique using Photometers (5010 V5+ Robert Riele). Determination of fasting blood glucose level using glucose oxidase and peroxidase (GOD-POD) method. This study found that 40% of alcohol drinker considered high fasting blood glucose level with an average level of 139.6 mg/dL. Twenty-five percent of alcohol drinkers regarded as low fasting blood glucose level with an average of 68.8 mg/dL. And 35% of drinkers have a normal level of fasting blood glucose with an average of 97.4 mg/dL